FORMULATION AND CHARACTERIZATION OF MODIFIED RELEASE TABLETS CONTAINING ISONIAZID USING SWELLABLE POLYMERS - Akhtar, M.; Rabbani, M.; Sharif, A.; Akhtar, B.; Saleem, A.; Murtaza, G. (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The aim of this work was to develop swellable modified release (MR) isoniazid tablets using different combinations of polyvinyl acetate (PVAc) and sodium-carboxymethylcellulose (Na-CMC). Granules were prepared by moist granulation technique and then compressed into tablets. In vitro release studies for 12 hr were carried out in dissolution media of varying pH i.e. pH 1.2, 4.5, 7.0 and 7.5. Tablets of all formulations were found to be of good physical quality with respect to appearance (width and thickness), content uniformity, hardness, weight variation and friability. In vitro release data showed that increasing total polymer content resulted in more retarding effect. Formulation with 35% polymer content exhibited zero order release profile and it released 35% of the drug in first hr, later on, controlled drug release was observed upto the 12th hour. Formulations with PVAc to Na-CMC ratio 20:80 exhibited zero order release pattern at levels of studied concentrations, which suggested that this combination can be used to formulate zero order release tablets of water soluble drugs like isoniazid. Korsmeyer-Peppas modeling of drug release showed that non-Fickian transport is the primary mechanism of isoniazid release from PVAc and Na-CMC based tablets. The value of mean dissolution time decreased with the increase in the release rate of drug clearly showing the retarding behavior of the swellable polymers. The application of a mixture of PVAc to Na-CMC in a specific ratio may be feasible to formulate zero order release tablets of water soluble drugs like isoniazid.